Pendekatan Pembelajaran Mendalam (Deep Learning) dalam Kebijakan Pendidikan Agama Islam untuk Pembentukan Karakter Siswa: Sebuah Studi Literatur - Dadang Abdul Qodir; Arpa Ismail Albar; Jalaludin Jalaludin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Islamic Religious Education (PAI) plays a fundamental role in students' character building, yet its implementation is often still trapped in a surface learning model oriented towards rote memorization. In line with educational policies in Indonesia that now emphasize the Deep Learning approach, an analysis of the alignment between PAI policies and this new approach is needed. This research uses a systematic literature review method with a qualitative approach. Data were collected from various empirical research articles published between 2022-2025. The method used is library research with a content analysis approach to various relevant scientific literature. The study results show that the principles of Deep Learning namely meaningful, mindful, and joyful learning are highly consistent with the goals of PAI to internalize moral values. However, there are challenges at the policy level, which often still focus on achieving curriculum content targets rather than facilitating a deep learning process. In conclusion, for PAI to be effective in character building, existing policies need to be reoriented to explicitly support and facilitate learning models that are contextual, reflective, and student-centered, in accordance with the essence of Deep Learning.